High gain switched beam Yagi-Uda antenna for millimeter wave communications. Issue 3 (14th December 2020) - Aylapogu, Pramod Kumar; Donga, Madhu Sudan; D., Venkatachari; B., RamaDevi
Abstract : Purpose: The suggested antenna has a switched mechanism among the successive elements of the radiating patch. The purpose of this paper is to develop high gain and less interference at higher frequencies. Design/methodology/approach: The design geometry of the suggested high gain switched beam Yagi-Uda antennas. The constructed antenna has been developed with Rogers Substrate, relative permittivity (εr ) of 4.4, tangent of loss 0.0009 and with height of 1.6 mm. The proposed antenna has an input impedance of 50, and it is connected to input feed line with 2 mm. Findings: In forthcoming life, the antennas play key role in all the wireless devices, because these devices perform with high gain and high efficacy. Originality/value: The pivotal principle of this paper is to accomplish the gain as high, high directivity and interference is low at higher frequencies. Therefore, it is more applicable to 5G mobile communications and millimeter wave communications.